Efforts To Improve Teacher Competence In Developing Learning Implementation Plans Through Continuous Guidance - Isman Isman (Fakultas Sastra Universitas Ekasakti, 2017)
To be able to learn something well, we need to hear, see, ask questions about it, and speak with others. Not only that, teachers need to